PENGARUH METODE PEER TEACHING TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA DISEKOLAH MENENGAH PERTAMA NEGERI 55 MERANGIN - Derista, Yenny; Oktarina, Yulia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the effect of the peer teaching method on students' learning outcomes in Islamic Religious Education at SMP Negeri 55 Merangin. The study was conducted because students' learning outcomes and classroom participation were relatively low under conventional teacher-centered instruction. A quantitative approach was employed using a quasi-experimental method with a nonequivalent control group design. The sample consisted of 40 eighth-grade students, with 20 students in the experimental class and 20 students in the control class. The experimental class was taught using the peer teaching method, while the control class received conventional instruction. Data were collected through pretest and posttest learning achievement tests and analyzed using normality, homogeneity, and Independent Samples T-Test with the assistance of SPSS software. The findings showed that the mean pretest scores of the experimental and control classes were 70.00 and 68.00, respectively. After the treatment, the mean posttest score of the experimental class increased to 91.00, while the control class reached 79.00. The results of the normality and homogeneity tests indicated that the data met the assumptions for hypothesis testing. Furthermore, the Independent Samples T-Test produced a significance value of 0.001 (< 0.05), indicating a statistically significant effect of the peer teaching method on students' learning outcomes in Islamic Religious Education. Therefore, the peer teaching method was proven to be more effective than conventional teaching in improving students' learning outcomes.